2014
DOI: 10.1371/journal.pone.0106800
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Reference Genes for Quantitative Real-Time PCR in Drosophila suzukii (Diptera: Drosophilidae)

Abstract: To accurately evaluate gene expression levels and obtain more accurate quantitative real-time RT-PCR (qRT-PCR) data, normalization relative to reliable reference gene(s) is required. Drosophila suzukii, is an invasive fruit pest native to East Asia, and recently invaded Europe and North America, the stability of its reference genes have not been previously investigated. In this study, ten candidate reference genes (RPL18, RPS3, AK, EF-1β, TBP, NADH, HSP22, GAPDH, Actin, α-Tubulin), were evaluated for their sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 31 publications
2
67
0
Order By: Relevance
“…In Drosophila , it has been shown that a larger panel of reference genes is required as the sample size and inherent complexity grows616263. Selection of gene types is also crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila , it has been shown that a larger panel of reference genes is required as the sample size and inherent complexity grows616263. Selection of gene types is also crucial.…”
Section: Discussionmentioning
confidence: 99%
“…), and Drosophila suzukii (Zhai et al . ). In particular, in Drosophila melanogaster , the expression stability of several housekeeping genes has been evaluated in various sample conditions, such as injury, heat stress, different diets, different ages, and neurodegeneration (Ling & Salvaterra ; Ponton et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, considering the high sensitivity of PCR, appreciable errors in data interpretation can occur when using qRT‐PCR to determine the transcript levels of target genes among various sample conditions, such as different tissues, treatments, amount of extracted RNA, and PCR amplification efficiencies (Ling & Salvaterra ; Zhai et al . ; Moon et al . , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Tephritidae family there are two studies on the oriental fruit fly, Bactrocera dorsalis 1718 and one in the West Indian fruit fly Anastrepha obliqua 19. Among other dipteran species, there are three studies on Drosophila melanogaster 152021 and a single one on each of D. suzukii 22, Musca domestica 23, Lucilia cuprina 24 and the Calliphoridae family25. Interestingly, there are no studies published on any mosquito species.…”
mentioning
confidence: 99%